Armistice and Germany's food supply 1918-19 : a study of conditional surrender - Menne, Bernhard (London New York Melbourne : Hutchinson & Co., 1944)
Bibliotheek Camille Huysmans
Dedicator: Menne, Bernhard, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: Wereldoorlog 1; voedselprobleem; vredesinitiatieven; Duitsland